Success and Failure of CRM Programme - Singhal, Sandeep (Journal of Commerce and Trade, 2013)
CRM, in the present times has become a big marketing strategy. It is gaining momentum with the increase of consumerism in the service sector CRM is the focal point or locus of the business. In the present article, the author has discussed all about CRM and the benefits which occur to the business firm as well as the customer. The author has also discussed some constraints and difficulties which arise in CRM and finally he has tendered useful suggestions to get success in this venture. That India’s mutual trade and trade intensities are increasing over the period of time, study explores that after the existence of SAARC Preferential Trading Arrangement (SAPTA) and establishment of World Trade Organisation, mutual trade and trade intensities of export and import are increasing and also more than the desired level.